A two dimensional fluid dynamics solver for use in multiphysics simulations of gas cooled reactors - Lockwood, Brian Alan (Georgia Institute of Technology, 2008)
Currently, in the field of reactor physics, there is a drive for high fidelity, numerical simulations of reactors for the purposes of design and analysis. Since the behavior of a reactor is dependent on various physical phenomena, high fidelity simulations must be able to accurately couple these different types of physics. This is the essence of multiphysics simulations. In order to accurately simulate the thermal behavior of a reactor, the physics of neutron transport must be coupled to the fluid flow and solid phase conduction occurring within the reactor. This thesis develops a computational fluid dynamics solver for this purpose. The solver is based on the PCICE solution algorithm and employs cell-centered finite volumes. In addition to the fluid dynamics solver, a newly developed form of conjugate heat transfer is implemented. This implementation tightly couples the physics of solid phase heat conduction with the fluid dynamics in an efficient and consistent manner. Finally, the radiation transport code EVENT is used to provide heat generation data to the fluids solver. Using this fluids solver, several benchmark problems are analyzed and the formulation is validated.